Increased number of responses may account for reduced resurgence following serial training. Issue 3 (6th February 2020) - Diaz‐Salvat, Claudia C.; St. Peter, Claire C.; Shuler, Natalie J.
Abstract : Abrupt discontinuation of functional communication training can cause resurgence of challenging behavior. Teaching multiple alternative responses in sequence ( serial training ) may reduce resurgence, relative to teaching a single alternative. However, previous evaluations of serial training included a different number of response options across comparison conditions. In Experiment 1, we varied both training type (single and serial) and number of response options, and replicated previous findings showing that more resurgence occurred following single training relative to serial training. In Experiment 2, we varied the training type while holding the number of alternative responses constant and obtained no consistent differences in resurgence. In Experiment 3, we varied the number of alternative responses while holding training type constant (i.e., single). More resurgence occurred in the condition with fewer response options, suggesting that the number of available alternative responses, and not explicit serial training of alternatives, was critical to outcomes.